1987
DOI: 10.1002/em.2850100408
|View full text |Cite
|
Sign up to set email alerts
|

Increased chromosome damage in pediatric heart catheterization patients after diagnostic fluoroscopy and cineangiography

Abstract: Chromosome damage (CD) and sister chromatid exchange (SCE) levels were studied in lymphocytes from 30 pediatric heart catheterization patients receiving radiation during diagnostic fluoroscopy and cineangiography procedures. Forty-eight-hour CD and 72-hr SCE cultures were prepared from sequential samples taken from each patient: samples 1-3 via the catheter the same day (1) before exposure, (2) after fluoroscopy, and (3) after cineangiography; and sample 4 by venipuncture the next morning. Significant increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Shafer et al 19 reported that increased chromosomal damage levels are correlated with both the radiation dose of cineangiography exposure and the volume of contrast medium in pediatric patients. Norman et al 20 demonstrated that only short RCM exposure does not lead to chromosome damage in cells and the effect of RCM is enhanced by the radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Shafer et al 19 reported that increased chromosomal damage levels are correlated with both the radiation dose of cineangiography exposure and the volume of contrast medium in pediatric patients. Norman et al 20 demonstrated that only short RCM exposure does not lead to chromosome damage in cells and the effect of RCM is enhanced by the radiation.…”
Section: Discussionmentioning
confidence: 99%